An investigation of the effectiveness of two different methods in teaching surgical aseptic skills: a quasi-experimental study - Esma Ozsaker; Burcak Sahin Koze; Yelda Candan Donmez; Eda Dolgun; Turkan Ozbayir; Meryem Yavuz Van Giersbergen; Fatma Demir Korkmaz (BMC Surgery)
Abstract Background It is of the utmost importance in the prevention of infections in surgery that nursing students should learn surgical aseptic skills fully and in the correct order. There is a need for innovative teaching strategies to ensure that the contents of students’ skills education are the same and that instruction is similar. Therefore, this study was conducted to investigate the effectiveness of two different methods in teaching surgical aseptic skills. Methods A quasi-experimental research design was used. A total of 67 students were included in the study, 35 in an intervention group (video-assisted teaching), and 32 in a control group (skill demonstration) were recruited in the nursing faculty of a university in Türkiye. In both groups, the level of aseptic skill knowledge, the level of psychomotor skill, and the satisfaction score were assessed. Results Although the students’ surgical aseptic technique pre-test knowledge scores were higher in the control group, the post-test knowledge scores of both groups were high, and no significant difference was found between the groups. It was found that the gown and glove-wearing post-test scores of the students in the intervention group were higher than those of the control group. The students’ sterile technique and surgical hand-washing skill levels were higher in the intervention group, and satisfaction with the teaching method was higher in the control group. Conclusions The conclusions of this study show that the results of interactive video teaching in teaching nursing skills are as good as the traditional face to face demonstration method. This is a positive indicator, suggesting that interactive videos can suitably be integrated into basic nursing skills training.